Kajian Rumput Laut Sargassum duplicatum J. G. Agardh sebagai Penghasil Bioetanol dengan Proses Hidrolisis Asam dan Fermentasi - Saputra, Dion Ragil; Ridlo, Ali; Widowati, Ita (977-2407769)
Bioethanol is an alternative fuel made from biomass containing sugar components, starch, and cellulose. So far, bioethanol is made from raw materials which become a source of food and feed resulting in the competition. The potential of cellulosic biomass seaweed S. duplicatum as bioethanol production can be a solution to resolve the issue. The purpose of this research was to study seaweed S. duplicatum J.G. Agardh as raw material for bioethanol. Method used for this research was experimental laboratory with a completely randomized design (RAL) factorial pattern to test glucose levels and a randomized block design (RAK) to test the ethanol levels. Ethanol concentration was determined by Gas Chromatography (GC). Hydrolysis with H2SO4 concentration of 0.2 M, 0.3 M, 0.4 M, 0.5 M and the variation within 30 minutes, 60 minutes, 120 minutes. The fermentation conducted with yeast S. cereviceae with incubation time 24 hours, 48 hours, 72 hours. Ethanol concentration measurements conducted using Gas Chromatography (GC). The results showed that the best conditions for hydrolysis of concentrated H2SO4 0.4 M (28.051 mg / ml ± 1.100) and 120 minutes (23.128 mg / ml ± 6.069). During the fermentation process, the maximum ethanol levels achieved at 72 hours incubation time is 0.0451% v / v ± 0.0098